EVALUASI EFEKTIVITAS BAKTERI BACILLUS MEGATERIUM SEBAGAI MATERIAL INJEKSI SELFHEALING UNTUK PERBAIKAN RETAK BETON - Alimin, Baso Muhammad Ilham; Muhammad Mauludin, Luthfi; Gandhi Widiarnoko (Politeknik Negeri Semarang, 2025)
Concrete deterioration is a significant problem in the construction industry, which can reduce the service life and structural performance of buildings. Conventional repair methods, such as the use of epoxy and other bonding materials, are commonly used to improve the durability of concrete, but often rely on synthetic materials that are not environmentally friendly. This study focuses on the use of Bacillus megaterium bacteria combined with epoxy as a self-healing injection material, offering an environmentally friendly and sustainable solution to overcome concrete cracking. This study explores the potential of Bacillus megaterium to biologically repair concrete structures by adding the bacteria to epoxy at concentrations of 5%, 10%, 15%, 20%, and 25%. Concrete blocks measuring 100 mm x 100 mm x 500 mm were tested using flexural strength, ultrasonic wave velocity (UPV), and scanning electron microscopy (SEM) tests to assess the effectiveness of the repair. The results showed that at a concentration of 15%, Bacillus megaterium increased the flexural strength by 12.19% of the initial strength and the UPV velocity reached 3.19 km/s, which was almost equivalent to normal concrete. SEM analysis showed the formation of calcium carbonate deposits on the cracks, indicating the success of the self-healing process. This study shows that the application of Bacillus megaterium in epoxy provides an environmentally friendly alternative to conventional concrete repair methods, reduces dependence on synthetic chemicals, and extends the service life of concrete infrastructure. This innovation contributes to the development of more sustainable and efficient construction practices in civil engineering.